2020
DOI: 10.1111/1365-2435.13586
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids link forest type to local abundance in tropical birds

Abstract: Selective logging is a major driver of environmental changes in the tropics. Recently, there has been increasing interest in understanding which traits make bird species resilient or vulnerable to such changes. Physiological stress mediated by the steroid hormone corticosterone (CORT) might underlie changes in local abundance of species because it regulates a range of body functions and behaviours to maintain homeostasis in changing environments. We conducted a 3‐year study to assess (a) the variation in CORT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…The inclusion of phylogeny in the LMs (see Supporting Information) did not change significantly the outcomes, thus we report only results of non‐phylogenetic models. To estimate the RPA index of each species, we used captures data of birds for each type of forest relative to our study period, as follows: ([captures in logged forest – captures in unlogged forest]/[captures in logged forest + captures in unlogged forest]; inverse of logging sensitivity index; Hamer et al., 2015; Messina, Edwards, Marasco, et al, 2020). Positive values of the RPA index indicate higher abundance of the species in selectively logged forest compared to unlogged forest.…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion of phylogeny in the LMs (see Supporting Information) did not change significantly the outcomes, thus we report only results of non‐phylogenetic models. To estimate the RPA index of each species, we used captures data of birds for each type of forest relative to our study period, as follows: ([captures in logged forest – captures in unlogged forest]/[captures in logged forest + captures in unlogged forest]; inverse of logging sensitivity index; Hamer et al., 2015; Messina, Edwards, Marasco, et al, 2020). Positive values of the RPA index indicate higher abundance of the species in selectively logged forest compared to unlogged forest.…”
Section: Methodsmentioning
confidence: 99%
“…A meta-analysis of avian response to logging revealed that species also have lowered immunity in logged forests in comparison with old-growth forests (Messina et al 2018), and were likely to carry higher disease loads. Furthermore, glucocorticoid levels have been shown to have carry-over effects on population dynamics in many bird species (Harms et al 2015; Hansen et al 2016; Messina et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Research into ruffed grouse ( Bonasa umbellus ) found that fecal cort metabolite (FCM) levels differed based on an individual’s roosting location and that FCM concentrations decreased as snow depth increased ( Shipley et al, 2019 ; Shipley et al, 2021 ). Messina et al (2020) found that feather cort level predicted relative abundance of several tropical bird species for the year following sampling, and the trend was stronger in logged forests compared to undisturbed forest areas. Research on black grouse ( Tetrao tetrix ) using FCM concentrations showed that disturbance by recreational winter activities could increase daily energy expenditure by as much as 10% ( Arlettaz et al, 2015 ).…”
Section: Introductionmentioning
confidence: 90%